Ecological imperative in the system of social responsibility of the society - Oleksandr Shybko (Cхід, 2013)
The author's concept of social responsibility locates in article as intrinsic sign of social being. Social responsibility appears as a dialectical unity of opposites - the freedom and necessity, the degree of freedom and the need to measure, which must comply with the requirements of all subjects of public relations, as the requirements of the law (measures is the law).